A PHONOLOGICAL ANALYSIS OF LEXICAL EVIDENCE FOR CONTACT BETWEEN AUSTRONESIAN AND YOLNGU PEOPLES - Keith, Evan Francis (Masyarakat Linguistik Indonesia, 2021)
Many conflicting theories exist concerning the ethnolinguistic identity of the Austronesian ‘trepanger’ traders who visited the north coast of Australia from the 17th century onwards. These competing hypotheses, invariably based largely on anthropological guesswork, are supported to varying degrees by lexical evidence in many of the languages of the Arnhem Land coast, especially Yolngu Matha. The central conceit of this paper is thus: by examining the relationships between words in Yolngu Matha and cognates that appear in Austronesian languages, it should be possible to make inferences about what languages were being spoken by traders on the Arnhem Land coast. Using this method, this paper contends that Makassarese and Bugis were most likely the predominant languages spoken by the trepangers, and that there is little evidence to support the various theories to the contrary.